The Tree of Life in Four Seasons: an Educational Application in the Archaeological Museum of Rethymno - Γαβριλάκη Ειρήνη; Τέγου Εύα (Education Sciences, 2021)
In this paper, we present a proposition of an alternative representation of objects with plant decoration in the Archeological Museum of Rethymno, undertaken in 2009, in the frame of the horizontal activity “The tree of life in four seasons”, proposed by the Ministry of Culture. For its realization we used an ensemble of tree motifs (olive tree, cypress, pomegranate and palm tree). Our target was to speak about the respect owed to nature and the landscape as reference place of a community and as frame of reference of the monuments. For the experience, the sentimental complicity (empathy) of the participants and the self-reflection on these subjects, we dramatized the ancient Greek myth of Erysichton.